The meaning of Yalta : - ed. by John L. Snell ; with a foreword by Paul H. Clyde. (Louisiana State University Press, 1956)
The struggle for a new order, by F.C. Pogue.--What to do with Germany? By J.L. Snell.--Russian power in Central-Eastern Europe, by C.F. Deizell.--Yalta and the Far East, by G.A. Lensen.--The Big Three and the United Nations, by F.C. Pogue.--Yalta in retrospect, by F.C. Pogue.